Genealogie statali? - Consoli, Giulia (Antropologia Pubblica, 2021)
In Italy, the definition of “unaccompanied foreign minor” was recently reaffirmed by Law 47/2017, which at the same time established the figure of “volunteer guardian”. This essay discusses both rhetoric and representations on this figure conveyed by some institutional actors and the performed experiences of a group of volunteer guardians in a northern Italian town. The description of this re-shaped guardianship as an expression of “social parenting” calls for an in-depth analysis of the extent of state regulatory intervention in the relational life definition of the foreign minors living in its territory. If volunteer guardianship is asked to fill a part of the alleged void since their not being considered, to some extent, someone's child, I propose to call the practices developed on volunteer guardians “State genealogies”. Consisting in the mobilisation of parental lexicon in an attempt to de-bureaucratise and personify the State and its institutions, “State genealogies” involve at once an anthropo-poietic project of de-kinning and resocialization. Drawing on an ethnographic fieldwork that took place from 2018 to 2021, I engaged the progressive difficulties in placing oneself in these genealogies and in acting out the shared parenting when faced with a scarce circulation of knowledge or an often limited conviviality. In the end, it is the call by the guardians themselves for anthropological contributions that closes this ethnographic path and opens up the possibility to outline a deeper involvement of anthropological knowledge and practices in these public spaces.